Distributed leadership and collective teacher efficacy, preventive factors of burnout syndrome: a study in teacher primary school in Chile - López Alfaro, Pablo Alfonso; Gallegos Araya, Verónica María; Maureira Cabrera, Óscar (Revista Complutense de Educación, 2022)
INTRODUCTION. Recent studies indicate that factors such as distributed leadership and collective teacher efficacy are significant elements that can affect the emotional state with which teachers face their educational work and may influence the appearance of burnout syndrome. In this context, the objectives of this research focus on analyzing the structural relationships between distributed leadership, collective teacher efficacy and burnout syndrome, in addition to investigating the mediation role played by collective teacher efficay between distributed leadership and burnout syndrome. METHOD. To achieve these objectives, the structural equations approach was used, which enabled both measurement models (item-construct relationship) and the structural model (relationship between latent variables) to be valued. In general, 432 questionnaires were collected from elementary school teachers, belonging to the Metropolitan Region of Chile. RESULTS. The results highlight that distributed leadership is related to high levels of collective teacher efficacy and low levels of burnout syndrome and that collective teacher efficacy plays a mediating role between both variables. DISCUSSION. In the study carried out, the relevance that leadership distribution practices have to develop high conditions of collective teacher effectiveness is emphasized, as a mediating variable, with the purpose of mitigating burnout levels in teachers.
Keywords: Leadership; teacher efficacy; burnout syndrome; elementary schools